Peningkatan kesehatan gigi dan mulut dengan pengendalian plak yang tepat pada anak SDN 51 Banda Aceh - Mardelita, Sisca; Keumala, Cut Ratna; Andriani, Andriani; Suryani, Linda; Liana, Intan; Nur, Arnela (Jurnal PADE: Pengabdian & Edukasi, 2024)
Plaque control is essential for the maintenance of healthy teeth and mouth. The habit of maintaining healthy teeth and mouth is influenced by knowledge and brushing techniques. Proper hygiene is essential for achieving dental and oral hygiene. Therefore, the delivery of dental and oral health education to students is very important to do. This community service aims to increase knowledge about controlling plaque and brushing teeth properly and correctly for children of State Elementary School 51 Banda Aceh. This community service is carried out using a descriptive method, with the target being all 51 grade V students of State Elementary School 51 Banda Aceh. The intervention provided was in the form of counseling on dental health and a demonstration of how to see and control plaque (how to brush your teeth properly and correctly). The results obtained by children's dental and oral hygiene status before the intervention were mostly in the very poor category (72%), while the results after the intervention were the child's dental hygiene status in the good category (84%). The conclusion was increased knowledge and improved dental and oral hygiene status.